Backgrounding the Paeroa Declaration - Jackson, Moana (2003)
Keywords: foreshore and seabed act 2004; hapū; iwi; protest

Kei a koe te tikanga - it's your choice; The history of the Māori seats - Mulholland, Malcolm (Karaka (Christchurch, N.Z.), 2006)
Notes that the five-yearly Maori Electoral Option, during which Maori voters may chose to be on either the general or Maori electoral rolls, runs f...
Keywords: elections; government; māori electorates; māori seats